Long‐term survival in triple‐vessel disease: Hybrid coronary revascularization compared to contemporary revascularization methods. Issue 10 (28th July 2020) - Basman, Craig; Hemli, Jonathan M.; Kim, Michael C.; Seetharam, Karthik; Brinster, Derek R.; Pirelli, Luigi; Kliger, Chad A.; Scheinerman, S. Jacob; Singh, Varinder P.; Patel, Nirav C.
Abstract: Background: Hybrid coronary revascularization (HCR) constitutes a left internal mammary artery graft to the left anterior descending (LAD) coronary artery, coupled with percutaneous coronary intervention (PCI) for non‐LAD lesions. This management strategy is not commonly offered to patients with complex multivessel disease. Our objective was to evaluate 8‐year survival in patients with triple‐vessel disease (TVD) treated by HCR, compared with that of concurrent matched patients managed by traditional coronary artery bypass grafting (CABG) or multivessel PCI. Methods: A retrospective review was undertaken of 4805 patients with TVD who presented between January 2009 and December 2016. A cohort of 100 patients who underwent HCR were propensity‐matched with patients treated by CABG or multivessel PCI. The primary endpoint was all‐cause mortality at 8 years. Results: Patients with TVD who underwent HCR had similar 8‐year mortality (5.0%) as did those with CABG (4.0%) or multivessel PCI (9.0%). A composite endpoint of death, repeat revascularization, and new myocardial infarction, was not significantly different between patient groups (HCR 21.0% vs CABG 15.0%, P = .36; HCR 21.0% vs PCI 25.0%, P = .60). Despite a higher baseline synergy between percutaneous coronary intervention with taxus and cardiac surgery(SYNTAX) score, HCR was able to achieve a lower residual SYNTAX score than multivessel PCI ( P = .001). Conclusions: In select patients with TVD, long‐term survival and FREEDOM from major adverse cardiovascular events after HCR are similar to that seen after traditional CABG or multivessel PCI. HCR should be considered for patients with multivessel disease, presuming a low residual SYNTAX score can be achieved.